Polyacrylamide‐based hydrogel coatings improve biocompatibility of implanted pump devices. Issue 7 (2nd March 2023) - Chan, Doreen; Maikawa, Caitlin L.; d'Aquino, Andrea I.; Raghavan, Shyam S.; Troxell, Megan L.; Appel, Eric A.
Abstract: The introduction of transcutaneous and subcutaneous implants and devices into the human body instigates fouling and foreign body responses (FBRs) that limit their functional lifetimes. Polymer coatings are a promising solution to improve the biocompatibility of such implants, with potential to enhance in vivo device performance and prolong device lifetime. Here we sought to develop novel materials for use as coatings on subcutaneously implanted devices to reduce the FBR and local tissue inflammation in comparison to gold standard materials such as poly(ethylene glycol) and polyzwitterions. We prepared a library of polyacrylamide‐based copolymer hydrogels, which were selected from materials previously shown to exhibit remarkable antifouling properties with blood and plasma, and implanted them into the subcutaneous space of mice to evaluate their biocompatibility over the course of 1 month. The top performing polyacrylamide‐based copolymer hydrogel material, comprising a 50:50 mixture of N ‐(2‐hydroxyethyl)acrylamide (HEAm) and N ‐(3‐methoxypropyl)acrylamide (MPAm), exhibited significantly better biocompatibility and lower tissue inflammation than gold standard materials. Moreover, when applied to polydimethylsiloxane disks or silicon catheters as a thin coating (45 ± 1 μm), this leading copolymer hydrogel coating significantly improved implant biocompatibility. Using a rat model of insulin‐deficient diabetes, we showed that insulin pumps fitted with HEAm‐ co ‐MPAm hydrogel‐coated insulin infusion catheters exhibited improved biocompatibility and extended functional lifetime over pumps fitted with industry standard catheters. These polyacrylamide‐based copolymer hydrogel coatings have the potential to improve device function and lifetime, thereby reducing the burden of disease management for people regularly using implanted devices.